The Effect of Resiquimod Levels on the Motility of Etawah Crossbreed Goat Spermatozoa Result from Separation - Citaliani Rostika, Yulia; Solihati, Nurcholidah; Setiawan, Rangga (Faculty of Animal Husbandry, Universitas Padjadjaran, 2024)
The study aims to determine the effect of resiquimod (R848) levels on the motility of spermatozoa of Etawah Crossbreed goats resulting from separation, and to determine the opimum level of use of resiquimod (R848) on the motility of spermatozoa of Etawah Crossbreed goats resulting from separation. The object used in this research was fresh semen from 4 years old Etawah Crossbreed goats. This research used a Completely Randomized Design method with 4 treatments (P0 = 0 µM R848, P1 = 0,3µM R848, P2 = 0,6 µM R848, dan P3 = 0,9 µM R848). Based on the research results, it shows that R848 has a significant effet on sperm motility in the lower layer but has no effect on sperm motility in the upper layer resulting from the separation. The research data was followed by the Duncan test. The result showed that motility of P3 (80,70%) was significantly lower than P0 (89,77%), P1 (89,52%), dan P2 (89,38%). It was cocluded that resiquimod (R848) had an effect on lower layer spermatozoa motility, with an optimum level of 0,3 µM in Etawah Crossbreed goat spermatozoa.